IgD Multiple Myeloma Paraproteinemia as a Cause of Myositis - I. Colombo; M. E. Fruguglietti; L. Napoli; M. Sciacco; E. Tagliaferri; A. Della Volpe; V. Crugnola; N. Bresolin; M. Moggio; A. Prelle (Neurology Research International)
A 48-years old man was diagnosed an IgD-k multiple myeloma (MM) at age 38 years for which he successfully underwent chemotherapy and bone marrow transplant. He then developed a graft-versus-host disease (GVHD) whose manifestations included, three years later, a polymyositis, diagnosed at muscle biopsy and successfully treated with steroids. Few months after polymyositis remission, myeloma relapsed and the patient was treated with thalidomide for six years with good remission. Soon after thalidomide suspension, MM relapsed again and the patient came to our observation for a new onset of neuromuscular symptoms. He underwent both muscle and peripheral nerve biopsy to discriminate between myositis (paraproteinemia versus GVHD), amyloidosis, and thalidomide toxicity. The first muscle biopsy showed an inflammatory pattern with necrotic fibres, macrophagical invasion (CD68 positive), rare interstitial cellular infiltrates (CD8 positive and CD4 negative), widespread anti-HLA positivity and negative antiMAC. The second muscle biopsy showed the same inflammatory pattern plus an involvement of blood vessels. Direct immunofluorescence for IgD showed diffuse positivity along the sarcolemmal in both muscle biopsies. Sural nerve biopsy demonstrated both demyelinating and axonal aspects with no inflammatory infiltrates, but positivity for HLA and MAC. Congo Red was negative in both skeletal muscle and peripheral nerve.